2020
DOI: 10.2147/jpr.s236812
|View full text |Cite
|
Sign up to set email alerts
|

<p>Ultrasound-Guided Stellate Ganglion Block for Central Post-Stroke Pain: A Case Report and Review</p>

Abstract: Background: Central post-stroke pain (CPSP) is refractory to pharmacotherapy (eg, NSAIDs, opioids, antidepressants, and anticonvulsants), and may require transcranial or deep brain stimulation. Case Presentation: A 67-year-old woman presented with severe paroxysmal cramp-like pain on the right side, including the head and both upper and lower extremities. The pain started 5 years earlier, was initially mild and occasional, but gradually intensified to an unbearable degree with an average of 10-15 daily episode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Moreover, neuropathic medications decreased by 50% in patients during follow-up visits. These results were similar to the case reports by Liao et al 7 and Liu et al 8 In both of their case reports, good pain relief lasting >6 months was obtained in patients with CPSP. However, our case series differs in the drugs used and the number of blocks administered.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, neuropathic medications decreased by 50% in patients during follow-up visits. These results were similar to the case reports by Liao et al 7 and Liu et al 8 In both of their case reports, good pain relief lasting >6 months was obtained in patients with CPSP. However, our case series differs in the drugs used and the number of blocks administered.…”
Section: Discussionsupporting
confidence: 91%
“…However, only 2 cases of stellate ganglion blocks used for treating refractory CPSP have been reported in the literature to the best of our knowledge. 7,8 This case series explores the role of stellate ganglion blocks in 5 patients with refractory CPSP.…”
mentioning
confidence: 99%
“…When applied to patients with upper limb spasticity after stroke, botulinum toxin has the effect of inhibiting nerve endings and secreting acetylcholine. Its drug lasts for a long time and its paralytic effect can effectively form new nerve terminals and reduce muscle tension [3] . The symptoms of upper limb spasticity after stroke are caused by the decline or disappearance of descending inhibition caused by the damage of upper motor neurons, resulting in different degrees of involuntary contraction of muscles, showing resistance to movement [4] .…”
Section: Resultsmentioning
confidence: 99%
“…Given the difficulty in translating medications targeting specific molecules in the neuroinflammatory cascade to the clinic, SGB targeting and affecting whole physiological networks is a promising approach for the treatment of CPSP. Actually, previous case studies have shown that SGB offers an effective intervention for CPSP, as the pain subsided rapidly in both intensity and frequency after SGB, and the quality of life was markedly improved [ 28 , 29 ]. Likewise, SGB was beneficial in the treatment of anxiety symptoms from post-traumatic stress disorder [ 70 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, SGB has emerged as a novel treatment for various pathological pain, such as complex regional pain syndrome, postoperative pain, and orofacial pain [25][26][27]. For CPSP, case studies showed that a single SGB treatment considerably alleviated somatic pain and decreased the usage of analgesic medicines in CPSP patients and that the analgesic effects of a single SGB therapy lasted at least one month [28,29]. However, the underlying analgesic mechanisms of SGB on CPSP remain unclear.…”
Section: Introductionmentioning
confidence: 99%